2011
DOI: 10.1371/journal.pone.0019775
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation and Recovery of Intracellular Ca2+ in Cerebral and Small Mesenteric Arterial Smooth Muscle Cells of Simulated Microgravity Rat

Abstract: BackgroundThe differential adaptations of cerebrovasculature and small mesenteric arteries could be one of critical factors in postspaceflight orthostatic intolerance, but the cellular mechanisms remain unknown. We hypothesize that there is a differential regulation of intracellular Ca2+ determined by the alterations in the functions of plasma membrane CaL channels and ryanodine-sensitive Ca2+ releases from sarcoplasmic reticulum (SR) in cerebral and small mesenteric vascular smooth muscle cells (VSMCs) of sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 30 publications
3
34
0
Order By: Relevance
“…In the presence of ryanodine, the KCl-induced Ca 2+ responses were still higher in HU conditions, confirming the increase in depolarization-induced Ca 2+ influx [50,51]. In our study, the increase in ST-bodipy(−)-DHP labeling further suggests that VDCC were expressed more and/or activated more in HU conditions, as previously observed in electrophysiology experiments [49,51].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the presence of ryanodine, the KCl-induced Ca 2+ responses were still higher in HU conditions, confirming the increase in depolarization-induced Ca 2+ influx [50,51]. In our study, the increase in ST-bodipy(−)-DHP labeling further suggests that VDCC were expressed more and/or activated more in HU conditions, as previously observed in electrophysiology experiments [49,51].…”
Section: Discussionsupporting
confidence: 90%
“…The result of this up-regulation of VDCC was the increase in Ca 2+ influx activated by depolarization (present study) and potentially the enhancement of angiotensin-II responses, as previously described [30] and recently suggested in the HU model [50]. Whatever triggered the response, the result is an increase in calcium influx and mainly an increase in CICR.…”
Section: Discussionsupporting
confidence: 80%
“…As for the mesenteric arteries, we did not found mitochondrial dysfunction in HU rats. Although the different changes in VSMCs ion channels (79) secondary to gravitational pressure gradient shifts in the circulation (4) have been indicated in differential vascular structural and functional remodeling during microgravity, the underlying mechanism remains to be established. Further studies are needed to investigate this question.…”
Section: Discussionmentioning
confidence: 99%
“…In mesenteric arteries, Colleran et al (12) demonstrated lower NE‐, KCl‐, and caffeine‐induced vasoconstriction, as well as decreased RyR‐2 mRNA and protein after 14 d of HU. In addition, ryanodinesensitive Ca 2+ release from the sarcoplasmic reticulum is decreased in vascular smooth muscle cells isolated from mesenteric arteries of HU rats (53). Thus, the mechanism of the microgravity‐induced impairment of mesenteric artery vasoconstrictor responsiveness in the present study appears to be consistent with that of ground‐based studies with HU rats.…”
Section: Discussionmentioning
confidence: 99%